The structural and biochemical basis of apocarotenoid processing by β-carotene-oxygenase-2 - Bandara, Sepalika (ACS Chem Biol, 2021)
In mammals, carotenoids are converted by two carotenoid cleavage oxygenases into apocarotenoids, including vitamin A. Although knowledge about β-carotene oxygenase-1 (BCO1) and vitamin A metabolism has tremendously increased, the function of β-carotene oxygenase-2 (BCO2) remains less well defined. We here studied the role of BCO2 in the metabolism of long chain β-apocarotenoids, which recently emerged as putative regulatory molecules in mammalian biology. We showed that recombinant murine BCO2 converted the alcohol, aldehyde, and carboxylic acid of a β-apocarotenoid substrate by oxidative cleavage at position C9,C10 into a β-ionone and a diapocarotenoid product. Chain length variation (C20 to C40) and ionone ring site modifications of the apocarotenoid substrate did not impede catalytic activity or altered the regioselectivity of double bond cleavage by BCO2. Isotope labelling experiments revealed that the double bond cleavage of an apocarotenoid followed a dioxygenase reaction mechanism. Structural modeling and site directed mutagenesis identified amino acid residues in the substrate tunnel of BCO2 that are critical for apocarotenoid binding and catalytic processing. Mice deficient for BCO2 accumulated apocarotenoids in their livers, indicating that the enzyme engages in apocarotenoid metabolism. Together, our study provides novel structural and functional insights into BCO2 catalysis and establishes the enzyme as key component of apocarotenoid homeostasis in mice.